Derivation Algebra of Quasi $R_n$-Filiform Lie Algebra (Communications in Mathematical Research, 2021)
In this paper we explicitly determine the derivation algebra of a quasi $R_n$-filiform Lie algebra and prove that a quasi $R_n$-filiform Lie algebra is a completablenilpotent Lie algebra.
Keywords: filiform Lie algebra; complete Lie algebra; derivation algebra.